Real-Time Neuropsychological Testing Protocol for Left Temporal Brain Tumor Surgery: A Technical Note and Case Report - Barbara Tomasino (Frontiers Media S.A., 2021)
Background: The risk of surgery in eloquent areas is related to neuropsychological dysfunctions. Maximizing the extent of resection increases the overall survival. The onco-functional balance is mandatory when surgery involves cognitive areas, and maximal information on the cognitive status of patients during awake surgery is needed. This can be achieved using direct cortical stimulation mapping and, in addition to this, a neuropsychological monitoring technique called real-time neuropsychological testing (RTNT). The RTNT includes testing protocols based on the area where the surgery is performed. We reported on tests used for left temporal lobe surgery and our RTNT decision tree.Case Report: We reported our RTNT experience with a 25-year-old right-handed man with 13 years of schooling. He reported daily partial seizures. MRI revealed the presence of a low-grade glioma involving the temporo-insular cortex. The neuropsychological status presurgery which was within the normal range was combined with functional magnetic resonance imaging (fMRI) and diffusion tensor imaging (DTI) information. Awake surgery plus RTNT was performed. Direct electrical stimulation during object naming elicited a motor speech arrest. Resection was continuously accompanied by the RTNT. The RTNT provided enriched information to the surgeon. Performance never dropped. A slight decrement in accuracy emerged for pseudoword repetition, short-term memory and working memory, phonological processing, and verbal comprehension. Total resection was performed, and the histological examination confirmed the nature of the lesion. Immediate postsurgery performance was within the normal range as it was the fMRI and DTI assessment.Conclusion: The RTNT provides essential information that can be used online, during surgery, for clinical aims to provide the surgeon with useful feedback on the cognitive status of patients.